Challenges in harvesting and utilization of Ziziphus tree fruits in Ethiopia - Tigabu R. Alle; Samora M. Andrew; Miriam F. Karlsson; Abdella Gure (Trees, Forests and People)
Ziziphus tree species commonly known as “jujube” are wide sources of nutritious and socio-economically important fruits in arid and semi-arid regions of Asia and Africa. However, understanding of local communities’ engagement in harvesting and utilization of these fruits remains limited consequently undermining sustainable harvesting and broader utilization. Household interviews (HHIs), focus group discussions (FGDs) and key informants’ interviews (KIIs) were used to investigate the level of harvesting and utilization of fruits from different tree species of jujube in Ethiopia. Multiple linear and binary logistic regressions were utilized to investigate factors influencing the annual fruit yield per tree and to discern factors impacting the local community's capacity to grow and sell jujube, respectively. Fruit yield per tree, market involvement and the principal challenges to growing were found to vary among two study sites. Bosset district's yield exceeded Bati's by 0.87 times. Women and children played significant roles in fruit collection, sale and management. Less rainfall reduced annual yield by 33 kg per tree while planting seedlings instead of relying solely on naturally regenerated trees boosted yield by 42 kg per year. With each advancing year in age, older respondents were 0.04 times less likely to sell harvested jujube fruits. The increasing impact of pests, water shortage and cultural influences decreased community interest in growing jujube by factors of 1.15, 1.41 and 2 times, respectively. Suboptimal involvement in jujube cultivation, fruit harvest and market activities was frequently ascribed to inadequate community support, organizational oversight and depressed market prices. These findings highlight the need to enhance awareness, management and market access for jujube fruits to broaden community benefits in Ethiopia.